2021
DOI: 10.1038/s41598-021-90463-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota dysbiosis and functional outcome in acute ischemic stroke patients

Abstract: Currently, few studies are reported on the composition of microbiota in stroke patients and the association with stroke prognosis. This study investigated the differing microbiota composition in stroke patients and confirmed the association of microbiota composition with poor functional outcome. Between January of 2018 and December of 2019, 198 patients with acute cerebral infarction were included in this study. For the case–control study, age and sex-matched normal healthy subjects (n = 200) were included whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Some fragmentary information is available on the involvement of Prevotella organisms in vascular conditions in the intracranial region. Regarding ischemic stroke, the genus Prevotella was found to be enriched in the patient group with poor treatment outcome [ 228 ]. DNA of P. intermedia has been recovered from ruptured intracranial aneurysm walls [ 229 ] and in culture of cerebrospinal fluid from a patient of intracranial mycotic aneurysm [ 230 ].…”
Section: Potential Involvement Of Oral Prevotella ...mentioning
confidence: 99%
“…Some fragmentary information is available on the involvement of Prevotella organisms in vascular conditions in the intracranial region. Regarding ischemic stroke, the genus Prevotella was found to be enriched in the patient group with poor treatment outcome [ 228 ]. DNA of P. intermedia has been recovered from ruptured intracranial aneurysm walls [ 229 ] and in culture of cerebrospinal fluid from a patient of intracranial mycotic aneurysm [ 230 ].…”
Section: Potential Involvement Of Oral Prevotella ...mentioning
confidence: 99%
“…Bacteria in the thrombus and plasma samples were similar, and 46.7% of thrombus bacteria may originate from plasma samples based on the FEAST algorithm. Previous studies have also detected bacterial fragments in the plasma of healthy individuals ( 28 ) and ischemic stroke patients ( 29 ), of which several bacteria were culturable ( 28 ). However, the sources of the circulating bacteria were uncertain in these previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…16S rDNA sequencing of intestinal microorganisms showed that f_Ruminococcaceae abundance increased most significantly in the immune-tolerant group ( Figure 3E ). This flora is closely related to nervous system diseases, such as Alzheimer’s disease, depression, and stroke ( Chang et al., 2021 ; Chen et al., 2021 ; Cuervo-Zanatta et al., 2021 ). Ruminococcus helps inhibit the translocation of bacterial products (e.g., LPS) into the blood, which may activate the Toll-like receptor 4 (TLR4), stimulate inflammatory responses, and secrete proinflammatory cytokines ( Shi et al., 2006 ; Cani et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%